1998
DOI: 10.1007/s005850050589
|View full text |Cite
|
Sign up to set email alerts
|

Case studies of the propagation characteristics of auroral TIDS with EISCAT CP2 data using maximum entropy cross-spectral analysis

Abstract: Abstract. In this paper case studies of propagation characteristics of two TIDs are presented which are induced by atmospheric gravity waves in the auroral F-region on a magnetic quiet day. By means of maximum entropy cross-spectral analysis of EISCAT CP2 data, apparent full wave-number vectors of the TIDs are obtained as a function of height. The analysis results show that the two events considered can be classi®ed as moderately large-scale TID and mediumscale TID, respectively. One exhibits a dominant period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…To date there have been very few reports showing the variability of MSTID parameters with altitude at high latitudes. These investigations mainly used ISR and ionosonde techniques, but with limited data and only one study at high latitudes using the EISCAT radar (e.g., Djuth et al, ; Ma et al, ; Nicolls et al, ; Oliver et al, ; Ratovsky et al, ; Tedd et al, ; Vadas, ). In particular Nicolls et al () reported TID height structure from Arecibo Observatory (18°N) obtained on two consecutive days (23–25 July 2009).…”
Section: Altitudinal Variabilitymentioning
confidence: 99%
“…To date there have been very few reports showing the variability of MSTID parameters with altitude at high latitudes. These investigations mainly used ISR and ionosonde techniques, but with limited data and only one study at high latitudes using the EISCAT radar (e.g., Djuth et al, ; Ma et al, ; Nicolls et al, ; Oliver et al, ; Ratovsky et al, ; Tedd et al, ; Vadas, ). In particular Nicolls et al () reported TID height structure from Arecibo Observatory (18°N) obtained on two consecutive days (23–25 July 2009).…”
Section: Altitudinal Variabilitymentioning
confidence: 99%
“…It is a statistical spectral analysis technique, which permits to enhance the resolution and signal/noise ratio of any measure on a given system. Owing to this priority, multichannel maximum‐entropy method was used by authors to determine TID propagation parameters [ Wan et al , 1998a; Ma et al , 1998]. The adoption of this method on GPS TEC array data was developed by Wan et al [1997].…”
Section: Propagation Of Lstids In North America Europe and Asia: Crmentioning
confidence: 99%
“…The major generation mechanism of LSTIDs is thought to be the energy input from the magnetosphere to the auroral ionosphere, such as Joule heating and particle precipitation during auroral substorms [ Crowley and Jones , ; Hajkowicz and Hunsucker , ; Bowman , ; Hajkowicz , , , ; Ma et al ., ; Afraimovich et al ., ; Afraimovich et al ., ; Afraimovich , ; Saito et al ., ; Shiokawa et al ., ; Tsugawa et al ., ; Tsugawa et al ., ; Tsugawa et al ., ; Hawlitschka , ; Ding et al ., ; Ding et al ., ; Ding et al ., ; Ogawa et al ., ; Crowley and Rodrigues , ; Nicolls et al ., ; Perevalova et al ., ]. Other possible excitation mechanisms have also been discussed by some authors.…”
Section: Introductionmentioning
confidence: 99%